Microplastic in Food and Drinking Water - Environmental Monitoring Data - Myszograj, Martyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Microplastics are present in the environment and have been found in seas and oceans, fresh water, sewage, food, air, and drinking water, both bottled and tap water. Nanoplastics can originate from engineered material or can be produced during fragmentation of microplastic debris.
Keywords: plastics; microplastics; monitoring; hazards; environment; tworzywa sztuczne; mikroplastik; monitorowanie; zanieczyszczenie; środowisko